Chlamydia psittaci Plasmid-Encoded CPSIT_P7 Elicits Inflammatory Response in Human Monocytes via TLR4/Mal/MyD88/NF-κB Signaling Pathway - Chen, Qian; Li, Yumeng; Yan, Xiaoliang; Sun, Zhenjie; Wang, Chuan; Liu, Shuangquan; Xiao, Jian; Lu, Chunxue; Wu, Yimou (Frontiers in Microbiology, 2020)
The chlamydial plasmid, an essential virulence factor, encodes plasmid proteins that play important roles in chlamydial infection and the corresponding immune response. However, the virulence factors and the molecular mechanisms of Chlamydia psittaci are not well understood. In the present study, we investigated the roles and mechanisms of the plasmid-encoded protein CPSIT_P7 of C. psittaci in regulating the inﬂammatory response in THP-1 cells (human monocytic leukemia cell line). Based on cytokine arrays, CPSIT_P7 induces the expression of interleukin-6 (IL-6), interleukin-8 (IL-8), and monocyte chemoattractant protein-1 (MCP-1) in THP-1 cells. Moreover, the expression levels of IL-6, IL-8, and MCP-1 stimulated by CPSIT_P7 declined after silencing of the Toll-like receptor 4 (TLR4) gene using small interfering RNA and transfection of a dominant negative plasmid encoding TLR4 (pZERO-hTLR4). We further demonstrated that transfection with the dominant negative plasmid encoding MyD88 (pDeNy-hMyD88) and the dominant negative plasmid encoding Mal (pDeNy-hMal) could also abrogate the expression of the corresponding proteins. Western blot and immunofluorescence assays results showed that CPSIT_P7 could activate nuclear factor κB (NF-κB) signaling pathways in THP-1 cells. Altogether, our results indicate that the CPSIT_P7 induces TLR4/Mal/MyD88/NF-κB signaling axis, and therefore contributies to the inflammatory cytokine response.